2018
DOI: 10.1063/1.5046185
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale shock-to-detonation simulation of pressed energetic material: A meso-informed ignition and growth model

Abstract: This work presents a multiscale modeling framework for predictive simulations of shock-to-detonation transition (SDT) in pressed energetic (HMX) materials. The macro-scale computations of SDT are performed using an ignition and growth (IG) model. However, unlike in the traditional semi-empirical ignition-and-growth model, which relies on empirical fits, in this work meso-scale void collapse simulations are used to supply the ignition and growth rates. This results in a macro-scale model which is sensitive to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 58 publications
3
74
0
Order By: Relevance
“…Wherever possible, fundamental information from experiment is also used. For energetic materials, this sequential approach is the one most commonly used for multiscale model development [5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Wherever possible, fundamental information from experiment is also used. For energetic materials, this sequential approach is the one most commonly used for multiscale model development [5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the p À v closure model well captured the ZND behavior when compared to the p À T closure model. However, the model for our microscale (9) requires the use of switch-on functions that are functions of temperature. To avoid the (numerically costly) fully iterative approach, we adopt the explicit model as outlined in Stewart et al [31].…”
Section: Full Papermentioning
confidence: 99%
“…We first examine the baseline case of A HS ¼ 2x10 17 W/m 3 , p s ¼ 7:21GPa, d ¼ 20 mm, and N HS ¼ 300: Although it is well known that voids have a distribution [8], here we only consider a single size due to grid resolution; it is straightforward to incorporate a distribution of pore sizes into the model. The hot-spots are initially randomly located within the crystal boundaries so that the power deposition term (9) is only active in these regions. Figure 17a plots pressure contours at one instance of time and shows that a detonation wave has formed.…”
Section: Figure 14mentioning
confidence: 99%
“…Considering the different numerical modelling and simulation efforts for heterogeneous explosives, many of these can be divided into one of two approaches. One approach is aimed at studying explosives initiation (mesoscale) [12][13][14][15][16][17][18], while the other is aimed at studying propagation (continuum) [19][20][21]. A third approach, atomistic simulations, is acknowledged here as it pertains to the mesoscale, but it is not discussed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Current research [12][13][14][15][16][17][18][19][20][21][22] is progressing to close this knowledge gap from both sides. Finite element analysis (FEA) and Eulerian/Lagrangian hydrocodes, together with modern computing resources allow for an image to computation approach for mesoscale modelling [12]; in this approach, microstructure images are obtained both experimentally and synthetically [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%